Strategi Menjadi Kepala Sekolah Profesional - Mohamad Muspawi (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The school principal is a teacher who is given the mandate or appointed as a leader in the school in a formal way, and has the task of empowering and giving examples in relationships that connect all citizens in the school, in order to improve the school they lead. The principal is demanded to always be a figure who can mediate, make decisions and solve problems can also make it as a source of information for the residents of the school they lead. A series of strategies that can be done to become a professional school principal are: 1). Obey the rules. 2). Taking the time. 3). Caring and responsive. 4). IT Utilization. 5). Academic Assistance. 6). Innovative.